A sustainable carbon footprint analysis for the city of Kuantan, Pahang Malaysia - Normah Abdul Latip; Mohd Umzarulazijo Umar (Malaysia Institute of Planners, 2022)
Carbon footprint is one of the critical elements in assessing the level of sustainability of an urban area or forest area. Cities are a vital contributor to climate change with 75 percent of global carbon emissions are from cities. Transportation, buildings and urban activities are among the most critical contributors of greenhouse carbon emission globally. The study aims to identify the current condition of total carbon produced in the study area. Geospatial and observation approaches with social distance and standard operation procedure were used during the data collection and fieldwork at the study area. Mapping analysis and survey were used to analyse the activities conducted and the carbon consumption level by visitors of the area. Preliminaries’ findings indicate that the visitors’ activities and carbon consumption were high within the existing green area at Esplanade Kuantan, Pahang.